Miscarriage by Expert - Glazebrook, Susan (Victoria University of Wellington Law Review, 2018)
This article examines the role expert evidence plays in court and some of the risks surrounding such evidence. Through the examination of several tragic cases of miscarriage of justice, this article warns of the dangers of relying unquestionably on expert evidence and calls for a careful consideration of the evidence as each case comes before the courts. The value of good forensic evidence in the investigation and prosecution of crime is nevertheless recognised.